STEP-BY-STEP SYSTEM FOR DENTAL CERAMIC AESTHETIC REHABILITATION OF ANTERIOR TEETH - Matos, Jefferson David Melo de; Rodrigues, Michael Frank; Franzoni, Mariane Aparecida Andrade; Pereira, Vinicius de Vasconcellos; Cabral, Guilherme; Barbosa, Adriano Baldotto; Schindler, Jonas Uiliam Rodrigues; Viaro, Thiago R V; Granjeiro Júnior, José Ionaldo Teles; Queiroz, Daher Antonio (Brazilian Journal of Implantology and Health Sciences, 2024)
Stratification in dental ceramics is an essential technique for creating aesthetic and functional dental restorations that accurately mimic the appearance and properties of natural teeth. It requires a deep understanding of the materials used and technical skills to ensure high-quality results. This study aims to describe an extensive rehabilitation protocol, through a short communication, the step-by-step process of the stratification technique. The goal is to explore the different techniques for fabricating ceramic restorations, with a special focus on the stratification technique, reviewing its processing methods and highlighting the advantages and challenges associated with this approach.